Physicochemical and control releasing properties of date pit (Phoenix dactylifera L.) phenolic compounds microencapsulated through fluidized‐bed method. Issue 3 (13th December 2022) - Afshari, Kasra; Javanmard Dakheli, Majid; Ramezan, Yousef; Bassiri, Alireza; Ahmadi Chenarbon, Hossein
Abstract: This study aimed to investigate the effect of different ethanol/water solvents on phenolic compound extraction and microencapsulated extract of date pit powder. The highest and the lowest amounts of total phenolic compounds were 742.37 and 236.07 mg GAE/g dm, respectively, observed in water–ethanol composite solvent (25% W: 75% E) and water solvent (100% W). In this regard, the highest and lowest values of IC50 were 6.83 and 0.90 μg/ml, measured in water solvent (100% W) and water–ethanol solvent (25% W: 75% E), respectively. In the second phase, using maltodextrin (10%, 20%, and 30% W/V) as the first layer, date pit extract was microencapsulated. Alhagi maurorum gum (10%, 20%, and 30% W/V) as the second layer and medium‐chain triglycerides (MCT oil) (15% W/W) as the third layer were used by a fluidized‐bed drying technique. By increasing temperature, the microencapsulated extract powder solubility was increased as well. In contrast, the moisture content, bulk density, tapped density, and compressibility index decreased. By increasing temperature, the maltodextrin and A. maurorum gum concentration, the coating efficiency, and the loading capacity of the samples increased initially and decreased eventually. Moisture content, powder solubility, bulk density, and compressibility index increased, with increasing maltodextrin concentration, however, tapped density decreased. The optimal physicochemical properties of the phenolic compounds' microcapsules were determined at 45°C and at a concentration of 20% of each of the maltodextrin and A. maurorum gum. According to scanning electron images, the powder particles were spherical and had a relatively smooth surface. Notably, the release rate of phenolic compounds reached its maximum (64%) after 24 h. Abstract : In this research, the date pit extract was fluidized bed and encapsulated by maltodextrin, Manna of Hedysarum gum, and MCT oil (as a hydrophobic layer). The effect of different parameters on the efficiency and the microencapsulation properties was studied. Resulted, encapsulated phenolic compounds can be used as functional food ingredients.